Bicyclic Boronate β‐Lactamase Inhibitors: The Present Hope against Deadly Bacterial Pathogens. Issue 5 (15th February 2021) - Lence, Emilio; González‐Bello, Concepción
Abstract: The use of β‐lactamase inhibitors in combination with β‐lactam antibiotics is an emerging area in drug discovery. This strategy allows the restoration of the therapeutic efficacy of these antibiotics in clinical use against multiresistant bacteria. These pathogens are drug resistant because they express β‐lactamase enzymes, which prevent the antibiotic therapeutic action by catalyzing the hydrolysis of the β‐lactam ring. These enzymes are quite diverse in both their structural architecture and hydrolytic capability, as well as in the mechanism of action. The ever‐increasing emergence of pathogens that are capable of coproducing different types of β‐lactamases has triggered the search for ultrabroad‐spectrum inhibitors capable of deactivating both serine‐ and metallo‐β‐lactamases. A recent breakthrough in this long‐pursued and unmet need is the discovery of bicyclic boronate inhibitors, specifically taniborbactam, VNRX‐7145, and QPX7728, which are currently under clinical development in combination with cefepime, ceftibuten, and QPX2014, respectively. The present article highlights the therapeutic potential of these inhibitors and their spectrum of efficacy is compared with those of other β‐lactam/β‐lactamase inhibitor combinations recently approved by the food and drug administration. The molecular basis of the ultrabroad‐spectrum of activity of boron‐based inhibitors is also discussed, on the basis of the available crystal structures and the results of computational studies. Abstract : This article highlights the therapeutic potential of recently developed bicyclic boronate inhibitors, such as taniborbactam (VNRX‐5133), VNRX‐7145, and QPX‐7728, for restoring the efficacy of β‐lactam antibiotics against multi‐drug resistant bacteria having distinct resistance mechanisms. The molecular basis of the ultrabroad‐spectrum of activity of these boron‐based inhibitors is discussed based on the available crystal structures, along with Molecular Dynamics simulation studies.